2009
DOI: 10.1002/dvg.20483
|View full text |Cite
|
Sign up to set email alerts
|

Malaria sporozoite antigen‐directed genome‐wide response in transgenic Drosophila

Abstract: Malaria kills a million people annually. Understanding the relationship between a causative parasite, Plasmodium falciparum, and the mosquito vector might suggest novel prevention approaches. We created and transformed into Drosophila two genes encoding, thrombospondin-related adhesive protein (TRAP) and circumsporozoite protein (CSP), found on the cell surface of Plasmodium sporozoites. To understand a model insect's response, we induced these proteins separately and together, performing whole genome microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A previous study has utilized the robustness of the Drosophila system to identify genes that regulate Plasmodium growth in the mosquito [56] . For our analysis, we utilized the dataset from E-MEXP-1859 which originally was a Drosophila dataset with Plasmodial genes knocked in to understand the function of two important Plasmodium invasion molecules [57] . The study used Drosophila , a model system, to understand the role of Plasmodial surface antigens in Plasmodium invasion.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has utilized the robustness of the Drosophila system to identify genes that regulate Plasmodium growth in the mosquito [56] . For our analysis, we utilized the dataset from E-MEXP-1859 which originally was a Drosophila dataset with Plasmodial genes knocked in to understand the function of two important Plasmodium invasion molecules [57] . The study used Drosophila , a model system, to understand the role of Plasmodial surface antigens in Plasmodium invasion.…”
Section: Resultsmentioning
confidence: 99%
“…One study found that in transgenic D. melanogaster with high levels of cell surface proteins of the Plasmodium sporozoites, the expression of immune related genes were affected, although the Toll pathway expression was repressed. 22 The PADMA database can help understand such results more clearly in the context of Drosophila immunity against natural pathogens and the pathogen's ability to suppress or evade host defense.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant and transgenic Drosophila lines are readily available at stock centers and have been extensively used to probe the interactions between pathogens and the Drosophila host. Drosophila loss-of-function immune response gene mutants have been used to examine the roles of the genes in the response to infection with various pathogens [11, (16, 19, 4043) and Table 2], and transgenic Drosophila have been used to monitor the activation of immune response pathways upon infection (44, 45) and to examine the effects of transgenically expressed pathogen proteins on the host (21, 26, 46). Microarray and proteomic platforms as well as RNA interference (RNAi) lines and libraries have been developed and used to perform genome-wide analyses of Drosophila responses, in whole animals (41, 4756) and in the well-established Drosophila cell culture lines, Schneider-2 (S2, embryonic-derived phagocytic cell) and malignant blood neoplasm (mbn-2) (5659).…”
Section: Melanogaster As a Model For Studying Host–pathogen Interamentioning
confidence: 99%
“…Pathogen genes can be expressed ubiquitously (26) or in specific fly tissues such as the fat body (21), wings (263), and eyes (264) by placing the transgene under the control of tissue-specific promoters. This has facilitated the identification of host cell targets of Plasmodium sporozite proteins (26), anthrax lethal factor and edema factor (263, 265), pertussis toxin (266), HIV-1 viral protein U (21), and Epstein-Barr virus immediate-early protein BZLF1 (264) (Table 1). …”
Section: Drosophila Infection Modelsmentioning
confidence: 99%
See 1 more Smart Citation